2022
DOI: 10.3390/genes13112052
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Diversity and Bacterial Interaction Network in Eight Mosquito Species

Abstract: Mosquitoes (Diptera: Culicidae) are found widely throughout the world. Several species can transmit pathogens to humans and other vertebrates. Mosquitoes harbor great amounts of bacteria, fungi, and viruses. The bacterial composition of the microbiota of these invertebrates is associated with several factors, such as larval habitat, environment, and species. Yet little is known about bacterial interaction networks in mosquitoes. This study investigates the bacterial communities of eight species of Culicidae co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Microbiome analysis found that Wolbachia and Acinetobacter were the major core members of the microbiome among these treatments. Though Acinetobacter is not capable of enhancing the biotic fitness of the host [60], it is abundant in mosquito [61] and in arrhenotokous parasitoid, Diglyphus wani [62]. The core member of Acinetobacter should be the result of the high rates of multidrug resistance and extensive drug resistance [63].…”
Section: Discussionmentioning
confidence: 99%
“…Microbiome analysis found that Wolbachia and Acinetobacter were the major core members of the microbiome among these treatments. Though Acinetobacter is not capable of enhancing the biotic fitness of the host [60], it is abundant in mosquito [61] and in arrhenotokous parasitoid, Diglyphus wani [62]. The core member of Acinetobacter should be the result of the high rates of multidrug resistance and extensive drug resistance [63].…”
Section: Discussionmentioning
confidence: 99%
“…There are several cases where Wolbachia and Asaia have been detected in the same mosquito (e.g. Schrieke et al 2022 Computational and Structural Biotechnology 1 , Hegde et al 2018 Frontiers in Microbiology 2 , da Silva et al 2022 genes 3 , Chen et al 2020 Frontiers in Microbiology 4 ) but they may not be occupying the same tissues, especially given that Asaia can be environmentally acquired and often resides in the gut. This study also does not provide sufficient evidence for a Wolbachia-Asaia coinfection.…”
mentioning
confidence: 99%